Contribution of Mobile Banking on Customer Satisfaction in Commercial Banks in Rwanda, Case Study of Banque Popularie du Rwanda Plc, Part of Atlas Mara/ Headquarters (2016- 2020) - Nyetera Ernest (Research Parks Publishers, 2023)
The research analysed the “Contribution of Mobile Banking on the Customer Satisfaction in Commercial Banks in Rwanda. Case Study of Banque Popularie du Rwanda Plc. Part of Atlas Mara/ Headquarters (2016- 2020)”. Research hypothesis was H0: Mobile Banking does not contribute to the Customer Satisfaction in Banque Popularie du Rwanda Plc. Part of Atlas Mara/ Headquarters. Specific objectives were: to analyse mobile banking services provided by BPR Plc; to assess the extent to which customers are satisfied of Security, Responsiveness, and Ease of use of mobile banking application by BPR Plc; and to find out the challenges and solutions of mobile banking experienced by customers of BPR Plc. A sample of 100 respondents was selected from a total population of from 92,961 users of Mobile Banking at BPR Plc using Yamane’s formula. Statistical data was collected using a questionnaire and qualitative data was collected through interview. The major findings are the following: (i) Three main categories of mobile banking services provided by BPR Plc are Accounting information (x̄ =3.72); transactions services (x̄ =3.21); and support services (x̄= 2.47). In overall, mobile banking services are accessed at high level (overall x̄ =3.13). (ii) Customers are satisfied of Security, Responsiveness, and Ease of use of mobile banking application at high extent respectively by overall mean values of x̄ =3.50; x̄ =3.13; and x̄ =4.00. (iii) Main challenges of mobile banking with BPR Plc include: inability to apply for loan using mobile banking (x̄ =4.00); weak protection of accounts (x̄ =4.00); limited accepted amount for transfer per day (x̄ =3.29); temporally server failure (x̄ =3.12); and limited number of ATM (x̄ =3.02). In overall, 97% of respondents agreed that mobile banking at PBR Plc increase customer satisfaction. This leads to reject the Null Hypothesis and accept alternative hypothesis. (iv) The research recommends: to encourage all customers shifting to mobile banking; to provide additional options to limit access by simple user name and password; to strengthen security face possible cyber- crimes; to adjust the amount of money to transfer upon demand; to allow access to small loans though Mobile banking; to improve server maintenance to avoid service shortage; to spread agents in main centers to allow access to cash; and to increase ATMs to reduce the queue at bank.